The role of plasma prolactin concentration in seasonal fibre growth cycles in down-producing goats and Wiltshire sheep : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Animal Science at Massey University - Litherland, A. J. (Massey University, 1996)
This study examined the role of plasma PRL concentration in regulating seasonal fibre growth following the transition from short to long day photoperiod. In three down goat genotypes higher proportions of Angora genes extended the duration of guard hair growth, decreased biannual down growth and reduced the period of secondary follicles inactivity. The timing of follicle reactivation in spring and seasonal changes in plasma PRL concentrations were similar in all genotypes. Plasma PRL concentration increase, in spring, was associated with primary, but not secondary, follicle reactivation. Secondary follicle reactivation produced down of less than 2 mm which was associated with the shedding of winter down. Plasma PRL concentrations were suppressed, in spring and long-photoperiods (16L:8D), by injections of 1-5 mg/goat/day of bromocryptine and 2-3 weekly injections of long-acting bromocryptine (Parlodel). Injections of 1-5 mg/goat/day of domperidone elevated plasma PRL concentrations for 12 hours by and shedding was advanced. The circulating half-life of PRL, in sheep and goats, was 42±6 and 104±14 minutes following PRL injection or constant infusion respectively. In down goats, the normal spring-rise in plasma PRL concentration was suppressed using Parlodel or advanced by long day photoperiod. Increased plasma PRL concentration in spring provided anagenic signals to telogen primary and secondary follicles and catagenic signals to anagen secondary follicles. Following a reversal from short to long photoperiod anagen follicles of both goats and sheep entered telogen. Shedding occurred when the follicles subsequently reactivated. The suppression of plasma PRL concentration using Parlodel, during long photoperiod reversal, prevented the catagenic effect of long-photoperiod on anagen Wiltshire sheep follicles. In goats, however bromocryptine did not prevent follicles entering catagen but delayed follicle reactivation. The intravenous infusion of PRL had no effect on fibre growth in down goats or Wiltshire sheep. While the direct infusion of PRL to the skin caused an extreme local tissue reaction. Plasma PRL concentration has a role in regulating seasonal fibre growth cycles in down-producing goats but it is not a simple causal relationship and is dependent on follicle growth stage.
Keywords: Plasma prolactin; Growth factors; Wool growth; Goats; Sheep